Qualitative Proteomics Analysis of Proteins and Biomarkers of Alzheimer’ Disease - Maheen Rasheed; Kashif Kareem; Aliha Liaquat; Aneela Ashraf; Sania Maryam (ASEAN Journal of Science and Engineering, 2022)
Alzheimer’sdementia (AD) is the plague of today's world: a costly harming illness that ransacks the elder of their capacity to work and affect their recollections. Many years of research have brought about a profound comprehension of the pathological processes and a range of targets of therapy. Proteomics has contributed enormously to these advances and will keep on having a growing role in determining the nature of obsessive injuries. Moreover, proteomics (both gel-based and gel-free, mass spectrometry-based), is probably going to assume an expanding job in distinguishing biomarkers that may aid early determination and in observing movement and above all response therapy. Alzheimer's dementia is a neurodegenerative disease characterized by limited motor functions and loss of memory. Clinically it is diagnosed by accumulation of plaques in neurons and formation of NFTs by the aggregation of tau proteins. These pathological changes in the brain can be observed in preclinical stages of AD known as ASYM AD and mild cognitive dementia.